Focus on the Beauty of Body: The Mediation Role of Body Appreciation Between Perfectionism and Body-Related Shame and Body-Related Guilt - Liang, Zhang; Lingting, Shen; Ying, Cai; Xiaoyan, Liu; Yan, Zhang; Ronghua, Ying; Dan, Bi; Yanqiang, Tao (Frontiers in Psychology, 2021)
Objectives: According to traditional views, perfectionists are prone to experience shame and guilt. As a relative part of negative body image, body appreciation reflects an appreciation attitude toward physical characteristics, functionality, and health, accepting and appreciating all parts and functions of the body, predicting body-related shame and guilt. Methods: Therefore, body appreciation was examined for its potential mediating role in the relationship between two dimensions of perfectionism (e.g., healthy perfectionism and unhealthy perfectionism) and body-related shame and body-related guilt among 514 females. Results: The results highlight that body appreciation partially mediated the relationship between perfectionism and body-related shame and body-related guilt. Implications for enhancing body appreciation among females between experiencing healthy or unhealthy perfectionism and body-related shame and body-related guilt feelings are discussed. Conclusions: These findings underscore the importance of considering body appreciation in addressing perfectionism dimensions and body-related shame and body-related guilt. Research and clinical implications are also addressed.